Implementation of East Kalimantan Provincial Regulation Number 5 of 2019 Concerning the Provision of Legal Aid for Underprivileged Communities in East Kalimantan - Isnawati, Isnawati; Putri, Dina Paramitha Hefni; Sandra, Dinda Widia (Borong Newinera Publisher, 2023)
Equality before the law and the right to obtain defense from an advocate is a fundamental human right and one of the essential elements in achieving justice for everyone. The East Kalimantan regional government provides legal aid to the poor based on East Kalimantan Provincial Regulation Number 5 of 2019 concerning the Implementation of Legal Aid. This study discusses issues regarding the implementation and challenges of East Kalimantan Provincial Regulation Number 5 of 2019 concerning the Implementation of Legal Aid. The writing of this thesis employs empirical research methods, utilizing both primary and secondary data sources. The results of this study indicate that the implementation of East Kalimantan Provincial Regulation Number 5 of 2019 concerning the Implementation of Legal Aid in Samarinda City has been carried out in accordance with the established regulations, but it has not yet been fully felt by some segments of the community. The challenges in implementing the regulation include budget limitations, lack of public awareness about the existence of legal aid, and insufficient outreach.